Mass-political work of party and Komsomol organizations of the city of Omsk on the formation of the 75th Stalinist volunteer separate rifle brigade of Omsk-Siberians (July–September 1942) - N. V. Leader (Омский научный вестник: Серия "Общество. История. Современность")
Based on an analysis of the activities of party and Komsomol organizations in the city of Omsk, the article shows the main directions and forms of mass political work carried out by local authorities to form the 75th Stalin volunteer separate rifle brigade of Omsk-Siberians. The author traces this activity from its beginning until the brigade was sent to the front. The study is conducted on the basis of a set of published and unpublished records of the Omsk city and regional committees of the All-Union Communist Party (Bolsheviks), the NKVD for the Omsk region and the memoirs of brigade veterans. It is carried out on the basis of a microhistorical approach, which made it possible to detail the features of mass political work in the process of forming a military unit during the Great Patriotic War. The article reveals the public mood of Omsk residents, which they demonstrated regarding the creation of a volunteer brigade. In conclusion, an assessment is made of the activities of party and Komsomol organizations in the city of Omsk and the most important principles of mass political work to form a brigade of Omsk-Siberians are formulated.